2008
DOI: 10.4103/0971-9261.44771
|View full text |Cite
|
Sign up to set email alerts
|

Congenital arhinia: A rare case

Abstract: Congenital arhinia or absence of nose is a rare condition with only 30 cases reported so far. We report a rare case and briefly review the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 7 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Moreover, Claudia et al [ 18 ] reported on a sister and brother who suffered from arhinia at the same time. Three mothers had medication during pregnancy: 2 of them [ 12 , 15 ] did not know about their medication and the other one [ 14 ] took a medicine called “escitalopram oxalate”. However, this baby was not born because pregnancy was terminated at the 29 th week [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Claudia et al [ 18 ] reported on a sister and brother who suffered from arhinia at the same time. Three mothers had medication during pregnancy: 2 of them [ 12 , 15 ] did not know about their medication and the other one [ 14 ] took a medicine called “escitalopram oxalate”. However, this baby was not born because pregnancy was terminated at the 29 th week [ 13 ].…”
Section: Discussionmentioning
confidence: 99%